ER-to-Golgi Transport: A Sizeable Problem. Issue 12 (December 2019) - McCaughey, Janine; Stephens, David J.
Abstract : Metazoans require efficient and ordered secretion of extracellular matrix (ECM) to coordinate cell and tissue function. Many ECM proteins are atypically large and their demand during key stages of development presents a major challenge to the canonical secretion machinery. While many of the molecular players in this pathway are known, little is understood about how they are integrated in time and space. Recent advances in gene engineering and super-resolution microscopy have underscored the spatiotemporal organisation of the endoplasmic reticulum (ER)–Golgi interface. These findings are challenging long-held models of vesicular transport of large matrix proteins, such as procollagen, and are implicating less well-defined carriers and direct interconnections between organelles. Here, we discuss current models describing the dynamics and mechanisms of ER–Golgi transport. Highlights: Export of cargo from the ER requires an adaptable system to accommodate cargoes of diverse size and shape. In metazoans, the secretion of collagens has been widely studied due to their large size. TANGO1 has emerged as a key player in assembling COPII-dependent machinery to drive export from the ER. The interplay between TANGO1 and the chaperone Hsp47 is central to understanding this process. New data and resulting models have challenged the 'large carrier' model and have led to questions of whether complete coating of carriers with COPII is needed.